Photosynthetic values and inorganic nutrient contents of Sungai Ibai, Trengganu. - Samsudin, Lokman; Salleh, Umar (1982)
Photosynthetic rates and nutn'ent content measurements of subsurface water samples at four predetermined stations of Sungai Ibai in Trengganu indicated that the wet monsoon pen'od lowers the values of the former while increasing the ammonium nitrogen, nitrate nitrogen and dissolved oxygen contents. A seasonal variation in net photosynthetic values is observed, being high during the dry season and low during the wet monsoon season. However the ammonium nitrogen content exceeds that of either nitrate nitrogen or reactive phosphorus the whole year through. In relation, the nitrite nitrogen content is insignificant. The occurrence of high nitrate nitrogen contents could be attributed to increased nitrification processes while that ofammonium nitrogen to bacterial mineralization or decomposition.